Insecticidal Potential of Baccharis Macraei Essential Oils: An Ecological Approach to Their Volatile Composition in Insect Management - Santander-Meyer, R (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Bioinsecticides based on essential oils (EOs) are promising alternatives for agricultural insect control. In this study, the main compounds of Baccharis macraei EOs from two geographical areas were identified using gas chromatography–mass spectrometry (GC-MS). The insecticidal potential against Drosophila melanogaster, Tenebrio molitor, and Galleria mellonella was evaluated, along with acetylcholinesterase (AChE) inhibition and molecular docking analysis. GC-MS analysis revealed oxygenated sesquiterpenes, such as spathulenol, caryophyllene oxide, and α-cadinol. The EO from Site 1 (S1) exhibited insecticidal activity with lethal dose 50 (LD50) values of 46.50, 465.76, and 241.2 µg/mL for D. melanogaster, T. molitor, and G. mellonella, respectively. The EO from Site 2 (S2) showed LD50 values of 74.81, 385.62, and 195.2 µg/mL for the same pests. AChE inhibition yielded inhibitory concentration 50 (IC50) values of 12.8 ± 0.13 µg/mL for S1 and 11.7 ± 0.07 µg/mL for S2. Molecular docking analysis revealed a strong binding energy between α-cadinol and AChE. These results highlight that EOs from B. macraei are effective and serve as a natural alternative to traditional insecticides. © 2025 by the authors.